Evaluasi gambaran radiografi CBCT fraktur kepala kondilus pada anak - Merry Annisa Damayanti; Azhari Azhari; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: was to evaluate the radiographic of CBCT fractures in the neck of condyle Case Report: 11 years old boy was referred from the emergency department of RSGM UNPAD for CBCT radiographic examination with a suspected clinical diagnosis of left condyle fracture. The patient had an accident falling while playing one day ago. The patient complained of pain in the left ear, pain when opening the mouth and experiencing facial asymmetry. The CBCT radiograph shows a fragment of the condyle head and has a medial displacement Conclusion: CBCT can see the fragments' location in the fracture and changes in size and position direction that occur, whereas conventional radiographs are very difficult to see the condition.